2020
DOI: 10.3390/ijms21217814
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Impact from IL-2, IL-7, and IL-15 on the Growth and Signaling of Activated CD4+ T Cells

Abstract: While CAR-T therapy is a growing and promising area of cancer research, it is limited by high cost and the difficulty of consistently culturing T-cells to therapeutically relevant concentrations ex-vivo. Cytokines IL-2, IL-7 and IL-15 have been found to stimulate the growth of T cells, however, the optimized combination of these three cytokines for T cell proliferation is unknown. In this study, we designed an integrated experimental and modeling approach to optimize cytokine supplementation for rapid expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 43 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…Other clinical trials (#NCT00586391 and #NCT00709033) and in vitro experiments have supported this observation. For example, IL-7 and IL-15 can induce naïve T-cells to expand into effector memory T subsets, preserve the stem memory T cell (TSCM) phenotype, and increase resistance to apoptosis following repetitive stimulation, while preserving the migration to secondary lymphoid organs [ 95 , 96 , 97 , 98 , 99 , 100 ]. Multiple studies showed that the addition of antioxidants such as N-acetylcysteine to the cell culture during the manufacturing process has also been shown to inhibit effector differentiation and promote the expansion of TSCM cells [ 101 , 102 , 103 ].…”
Section: Factors Influencing T-cell Persistence In Clinical Settingsmentioning
confidence: 99%
“…Other clinical trials (#NCT00586391 and #NCT00709033) and in vitro experiments have supported this observation. For example, IL-7 and IL-15 can induce naïve T-cells to expand into effector memory T subsets, preserve the stem memory T cell (TSCM) phenotype, and increase resistance to apoptosis following repetitive stimulation, while preserving the migration to secondary lymphoid organs [ 95 , 96 , 97 , 98 , 99 , 100 ]. Multiple studies showed that the addition of antioxidants such as N-acetylcysteine to the cell culture during the manufacturing process has also been shown to inhibit effector differentiation and promote the expansion of TSCM cells [ 101 , 102 , 103 ].…”
Section: Factors Influencing T-cell Persistence In Clinical Settingsmentioning
confidence: 99%
“…We found that our lentiDNA vaccine prototypes did efficiently co-express both vaccine antigens HIV-Env, SIV-Gag p27 (1476 for CAL-SHIV-IN − IRES IL-7 and 823 pg/mL for CAL-SHIV-IN − IRES IL-15) and the cytokines IL-7 and IL-15 (1654 and 125 pg/mL, respectively), which were released in the supernatant of transfected HEK 293T cells ( Figure 1 c,f and Figure 2 A,B). These lower concentrations of cytokines are compatible with physiologic functions but not with cytokine storm-like induction [ 41 ]. To evaluate the function of IL-7 and IL-15 released in the supernatant of transfected cells, we used our lab-adapted PHPC assay on human PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…IL-7 is a multifunctional cytokine, which can act on a variety of cells. The main function is to promote the development, antiapoptosis, and proliferation of immature B and T cells and to participate in the differentiation and maturation of thymocytes [ 38 , 39 ]. The biological effect of IL-7 is mainly achieved through the binding of IL-7 to the IL-7 receptor (IL-7R).…”
Section: Discussionmentioning
confidence: 99%